2017
DOI: 10.1071/sb16028
|View full text |Cite
|
Sign up to set email alerts
|

Petal epidermal micromorphology in holoparasitic Orobanchaceae and its significance for systematics and pollination ecology

Abstract: Flowers of holoparasitic plants have evolved several adaptations for pollination as part of their parasitic strategies. A study of the petal epidermis may be useful to systematics as well as to the knowledge of ecological and co-evolutionary adaptations between the parasites and their pollinators. The present work is a comparative study of the microsculpture of nectar guides and landing platforms in the flowers of holoparasitic species in the family Orobanchaceae. In total, 285 samples of 39 species from 10 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…The tepal epidermal cell surface patterns (i.e., papillose knobby striate cells vs. tabulate rugose cells with striations) as well as presence/absence of papillae on tepal could be an importance of taxonomic traits in Korean Disporum species. In general, tepal micromorphological characters in angiosperms are associated with plant‐pollinator interaction (Costa, Pimentel, Chagas, Alves, & Castro, 2017; Piwowarczyk & Kasińska, 2017), and could be useful for taxonomic identification in various groups (Barone Lumaga et al, 2012; Jang et al, 2014; Park et al, 2020). Although floral micromorphological characteristics have not been commonly assessed in taxonomic studies of the genus Disporum (Chen et al, 2000; Hu et al, 2016; Li et al, 2007; Zhu et al, 2016, 2019), we confirmed that the micromorphology of gynoecium such as stigma, style, ovary epidermal cell surfaces were useful for the identification for the four Korean Disporum species as reported in other plant groups of Liliaceae s.l .…”
Section: Discussionmentioning
confidence: 99%
“…The tepal epidermal cell surface patterns (i.e., papillose knobby striate cells vs. tabulate rugose cells with striations) as well as presence/absence of papillae on tepal could be an importance of taxonomic traits in Korean Disporum species. In general, tepal micromorphological characters in angiosperms are associated with plant‐pollinator interaction (Costa, Pimentel, Chagas, Alves, & Castro, 2017; Piwowarczyk & Kasińska, 2017), and could be useful for taxonomic identification in various groups (Barone Lumaga et al, 2012; Jang et al, 2014; Park et al, 2020). Although floral micromorphological characteristics have not been commonly assessed in taxonomic studies of the genus Disporum (Chen et al, 2000; Hu et al, 2016; Li et al, 2007; Zhu et al, 2016, 2019), we confirmed that the micromorphology of gynoecium such as stigma, style, ovary epidermal cell surfaces were useful for the identification for the four Korean Disporum species as reported in other plant groups of Liliaceae s.l .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the existence of specific petal epidermal types related to specific pollinators [1][2][3][4]6,[56][57][58]. The petals of melittophilous species, for instance, have conical cells on the adaxial epidermis [3,59], suggesting the existence of a mechanical interaction between the pollinators and the conical cells of melittophilous petals.…”
Section: Discussionmentioning
confidence: 99%
“…Broomrapes usually have a short flowering time, during which we can observe closed flower buds as well as fully developed flowers with a prominent stigma on one individual 6 . Flowers of parasitic plants are bisexual and show a number of adaptations to insect pollination, e.g., small flowers gathered in dense inflorescences with a contrasting colouration and shine of the corolla and stigma 10 – 13 .…”
Section: Introductionmentioning
confidence: 99%